Comparison of sustained low-efficiency dialysis and continuous renal replacement therapy in patients in the intensive care unit with acute kidney injury: A search for a safe and rapid therapeutic approach - Satyanarayana Garre; Swarna Deepak Kuragayala; Somashekar Mudigonda (Critical Care Innovations, 2025)
INTRODUCTION: In recent years, sustained low-efficiency dialysis (SLED) has emerged as a viable alternative to continuous renal replacement therapy (CRRT) for critically ill patients experiencing acute kidney injury (AKI). The aim of the study is to compare SLED with CRRT in patients with acute kidney injury (AKI). MATERIALS AND METHODS: This observational cohort was conducted in 52 patients with AKI, and all patients were assigned into two groups; sustained low-efficiency dialysis (SLED, n=26) and continuous renal replacement therapy (CRRT, n=26). Outcomes such as mortality, mechanical ventilation requirement and SOFA score at 0 hour and 48 hour of replacement therapy, cumulative fluid removal in 7 days following replacement therapy in were analysed. RESULTS: The morality at 30 days is 38.4% (10/26) in the SLED group and 57.7%(15/26) in the CRRT group. There were 19.2% and 23.07% of the cases dependent on dialysis at 30 days in CRRT and SLED groups (p<0.05). The mean SOFA score was higher in the SLED group than in the CRRT group at 0 hour (15.385 ± 0.451 vs. 14.846 ± 0.414). It was 15.5 ± 0.713 and 14.923 ± 0.612 in the CRRT and SLED groups at 12hrs (p>0.05). The mean SOFA score at 24 hours was 14.143 ± 1.214 and 13.955 ± 0.76 the in CRRT and SLED groups (p>0.05). After 48 hours of RRT initiation, SOFA drops to 10.813 ± 1.603 and 12.1 ± 0.948 in the CRRT and SLED groups (p<0.05). CONCLUSIONS: Primary outcome mortality was 57.7% cases in the CRRT group, while 38.4% in the SLED group (p=0.16). Secondary outcomes such as dialysis dependence at 30 days and early clinical deterioration, showed no difference across groups. SLED is a viable alternative to CRRT for hemodynamically unstable patients with AKI.